2018
DOI: 10.3390/met8060434
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Time Superposition Effect on Compressive Properties of AZ31B Magnesium Composite Foams

Abstract: Magnesium composite foams with 10 vol. % of hollow ceramic microspheres (CMs) were prepared by modified melt foaming method. Specimens with homogeneous pore structures were subjected to various heating temperature (150, 250, 320, 400, and 500 • C, respectively) and enduring times (1, 2, 4, 6, and 24 h, respectively). Evolution of microstructure and mechanical properties of the samples, before and after the heating processes were examined by applying X-ray diffraction technique (XRD), differential scanning calo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Moreover -like other metallic foams -AMSFs have good specific mechanical properties, which are isotropic contrary to liquid state produced 'conventional' metallic foams (because the lack of gravitational force effects, that has no role on the geometry of pores in the case of AMSFs). The matrix material of AMSFs is some kind of aluminium alloy usually; however, similar structures (in general metal matrix syntactic foams (MMSFs)) with steel [1,[3][4][5], magnesium [6][7][8][9][10][11][12][13], titanium [14][15][16][17] and zinc [18][19][20][21][22] matrices have also been reported. The filler or reinforcing hollow spheres can be ceramic or metallic in material and they are commercially available from specified providers, such as Hollomet GmbH [23], for example.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover -like other metallic foams -AMSFs have good specific mechanical properties, which are isotropic contrary to liquid state produced 'conventional' metallic foams (because the lack of gravitational force effects, that has no role on the geometry of pores in the case of AMSFs). The matrix material of AMSFs is some kind of aluminium alloy usually; however, similar structures (in general metal matrix syntactic foams (MMSFs)) with steel [1,[3][4][5], magnesium [6][7][8][9][10][11][12][13], titanium [14][15][16][17] and zinc [18][19][20][21][22] matrices have also been reported. The filler or reinforcing hollow spheres can be ceramic or metallic in material and they are commercially available from specified providers, such as Hollomet GmbH [23], for example.…”
Section: Introductionmentioning
confidence: 99%
“…The heat treatment methods commonly used for Mg alloys include annealing, solid solution strengthening and artificial aging. Xia et al [15] investigated how different heating temperatures and durations affected the evolution of microstructure and compressive properties of AZ31 Mg alloy. The results showed that due to the dissolution of the Aluminum-containing phases and the relieving of internal stresses, the alloy after heat treatment exhibited low microhardness, yield strength and energy absorption capacity.…”
Section: Introductionmentioning
confidence: 99%
“…This structure leads to higher relative density (~0.5) foams exhibiting outstanding compressive properties compared at least to the “conventional” open and/or closed cell metallic foams. MMSFs can be produced from any kind of metal in theory, but Al alloys are the most common [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ], but Mg [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ], Fe [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ], Ti [ 26 , 27 , 28 , 29 ], and even Zn [ 30 , 31 , 32 , 33 ]-based MMSFs can also be found in the literature. The filler material can also be various ranging from mixed oxide ceramics [ 15 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ] to high purity and quality alumina [ 41 , 42 , 43 , 44 ] or silicon carbide [ 2 , 10 , 12 ].…”
Section: Introductionmentioning
confidence: 99%